Thermodynamic analysis of hydrogen production via chemical looping steam methane reforming coupled with in situ CO2 capture. (January 2015) - Antzara, A.; Heracleous, E.; Bukur, D.B.; Lemonidou, A.A.
Highlights: Detailed thermodynamic analysis of sorption enhanced chemical looping reforming. CO2 sorption in the reformer leads to increased performance at low temperature. Addition of oxygen carrier leads to significant reduction of thermal requirements. The presence of the oxygen carrier slightly decreases hydrogen production. Abstract: In this study, a detailed thermodynamic analysis of the sorption enhanced chemical looping reforming of methane (SE-CL-SMR), using CaO and NiO as CO2 sorbent and oxygen transfer material respectively, was conducted. The effect of different parameters, such as reactor temperature, pressure, H2 O/CH4 ratio, CaO/CH4 ratio and CaO/NiO ratio was investigated. Moreover, the use of different sweep gases and oxidants for the re-oxidation/calcination cycle, like pure oxygen, air, steam and CO2, was specifically addressed. Conventional steam reforming (SMR) and sorption enhanced steam reforming (SE-SMR) were also investigated for comparison reasons. The results of thermodynamic analysis show that there are significant advantages of both sorption enhanced processes compared to conventional steam reforming. Presence of CaO sorbent in the reformer leads to higher methane conversion, hydrogen purity and yield at low temperatures (∼650 °C). Addition of the oxygen carrier, in the chemical looping reforming concept, minimizes thermal requirements of the process, and results in superior performance compared to SE-SMR and SMR processes. A negative effect from NiO addition is reduction in hydrogen production (due to the reaction of part of methane with NiO to form CO/CO2 ). Hydrogen yield is up to 11% lower compared to SE-SMR for a NiO/CaO ratio of 0.7. It was found that only pure O2 can be used for re-oxidation/regeneration in order to reduce the energy requirements of the SE-CL-SMR process up to 26% compared to SE-SMR and up to 55% compared to conventional SMR.